Digital Media Preferences of Hostel Backpacker Consumer in Bandung Using Recommendation Score - Aditia Sovia Pramudita (Competitive, 2020)
The tourism industry in Indonesia is potential growth in the future. Accommodation is one of the important supporting factors in order to develop the tourism industry. The accommodation sector is predicted to compete tightly. Hostel as one of accommodation selection also needs to be developed to fulfill a low-cost accommodation segment. In order to survive in this industry, Hostel practitioner should carefully choose their channel. In this era, digital media become one of the most preferable channel selection since it is considered costless. Even though, the use of digital channels should be considered carefully. Wrong digital channel selection can lead to opportunities lost sales which is a loss for the company. This research is conducted in Bandung focusing on Hostel consumers. The result of this research, for promotional channel Instagram is considered as the most recommended promotional channel for hostel consumers. While for the distribution channel, Agoda is considered as the most recommended distribution channel for hostel consumer.